Legal Consequences Of The Incompatibility Of The Dual Positions Of Notarits And Permanent Lecturers Based On The Asn Law And Notary Department Law - Handoko, Panggung (International Journal of Educational Research & Social Sciences, 2025)
This study discusses the legal impacts caused by the incompatibility of dual positions between notaries and permanent lecturers with the status of State Civil Apparatus (ASN), by referring to Law Number 2 of 2014 concerning the Position of Notaries and Law Number 5 of 2014 concerning ASN. The main focus of this study is to analyze the provisions prohibiting dual positions along with their legal consequences, including potential conflicts of interest, decreased quality of professionalism, and administrative sanctions that may be imposed. The approach used in this study is the normative legal method, with an emphasis on the analysis of laws and regulations and the review of legal documents. The research findings show that laws and regulations strictly prohibit the practice of dual positions in order to maintain the objectivity and integrity of notaries as public officials. Violation of this prohibition can have serious consequences, ranging from administrative sanctions to revocation of professional licenses. This study emphasizes the importance of enforcing legal provisions and the need for intensive supervision to prevent dual position practices that can damage the credibility of institutions and reduce public trust. The results of this study are expected to be used as consideration for policy makers and authorized agencies in strengthening the ASN management system and notary positions in Indonesia.